Masa hidup imago, progeni, dan kemampuan parasitisasi Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae), parasitoid kutu putih singkong - Maharani, Juwita Suri; Rauf, Aunu; Maryana, Nina (Perhimpunan Entomologi Indonesia, 2019)
Parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced from Thailand into Indonesia in early 2014 to control the invasive cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). Research was conducted in laboratory with the objectives to determine effect of honey on adult longevity, to study fecundity, progeny production, and sex ratio, and to evaluate effect of increased host density to parasitization. Studies were carried out by exposing 3rd instar nymphs of mealybug to parasitoids. Effect of honey on adult longevity was done in the absence of hosts. Fecundity was measured by the number of mummies formed. Results showed that adult females lived for 3.7 days, while males lived for 3.2 days when only provided water. Adult longevity increased significantly when honey was provided. Parasitoids with access to 50% honey lived almost six to nine fold longer than those provided water. Over its adult life, A. lopezi parasitized 96–287 mealybugs with an average of 203.7 or 34.6% of hosts were parasitized, and 24.86% were killed through host feeding. Development from egg to adult emergence required 17.97 and 17.67 days for males and females respectively. The average number of offspring produced per female was 88.8 individuals, of which 56.9% were females. The number of hosts parasitized at densities varying from 2–100 cassava mealybugs corresponded to a type III functional response.